Phenotypic detection of carbapenem-resistant Enterobacterales and carbapenem-resistant Pseudomonas aeruginosa by mCIM and eCIM and their ceftazidime-avibactam with aztreonam synergy profile in a tertiary care hospital in Eastern India - Payel Chanda; Sharmila Gupta; Saswati Chattopadhyay; Soma Bose (Asian Journal of Medical Sciences, 2024)
Background: Worldwide, the emergence of carbapenem-resistant enterobacterales (CRE) and carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a global concern to public health as they are responsible for several serious infections that lead to elevated treatment expenses, prolonged hospitalization, and a higher mortality rate. Aims and Objectives: To detect Carbapenem resistance in Enterobacterales and Pseudomonas aeruginosa by phenotypic methods such as mCIM and eCIM. To determine synergism between Ceftazidime-Avibactum and Aztreonum in metallobetalactamase producing isolates. Materials and Methods: Total 217 isolates including enterobacterales and Pseudomonas aeruginosa from patient’s samples such as urine, pus, blood, wound swab, sputum, and ET tube were processed as per standard protocol during the study period from July 2023 to January 2024 at Calcutta National Medical College, Kolkata. Results: Resistance to carbapenem was observed in 110/217 (50.69%) isolates. Phenotypically, 99/110 (90%) produced metallo-β-lactamase and 11/110 (10%) produced serine carbapenemase by mCIM with eCIM test. MBLs producing organisms were most commonly isolated from blood culture samples. On an average, 76% of the MBL producing isolates shows positive synergy result to the combination of CZA+AT by disk elution method. Conclusion: eCIM and mCIM test was performed for identification of carbapenemase producing CRE and CRPA, which causes serious infection in patients with no definitive treatment. The combination of CZA-AT is a potential treatment option to manage CRE and CRPA-associated infections.